A New Simplified Prediction Method of the Contact State between Shallow Foundations and Swelling Ground - Farid, Z.; Lamdouar, N.; Bouziyane, J. Ben (Salehan Institute of Higher Education, 2021)
Prediction of the contact state between soil and structure is a key step in any study of shallow foundations resting on swelling soil. However, in practice, the foundation designer has no simple and rapid method, at the design stage, to define the contact conditions. This study presents a new method, both simple and reliable, to predict the contact state. To do this, a soil-structure interaction model is developed. The building behavior is investigated with the Euler–Bernoulli beam theory and the ground behavior is investigated with a Winkler model. The soil-structure interaction is then, studied at the equilibrium state. The thereby obtained equation is analyzed and all of its parameters are synthesized in a new factor named